Polyamine Protocols - Morgan, David M. L. (Methods in Molecular Biology™, 1998)
David Morgan brings together in Polyamine Protocols a unique collection of hands-on enzyme assay techniques for the study of polyamines and their biological functions. The techniques range from assay methods for enzymes of polyamine biosynthesis and catabolism to measurements of polyamines, polyamine transport, and polyamine effects on cell growth. All methods are presented by active researchers who have developed them to a high degree of perfection in their own laboratories, and include clear, step-by-step instructions with numerous hints and tips to ensure readily reproducible results. Polyamine Protocols is the only compilation of methods currently available for use in studies involving polyamines. The collection offers both novice and experienced researchers across many fields-including cell and molecular biology, pharmacology, oncology, physiology, laboratory medicine, and clinical pathology-all the tools needed to elucidate the biological roles played by these ubiquitous substances